Natural products from traditional medicine as promising agents targeting at different stages of oral biofilm development - Chi, Yaqi; Wang, Ye; Ji, Mengzhen; Li, Yanyao; Zhu, Hualing; Yan, Yujia; Fu, Di; Zou, Ling; Ren, Biao (Frontiers in Microbiology, 2022)
Oral cavity is an ideal habitat for more than 1000 species of microorganisms. The diverse oral microbes form biofilms over the hard and soft tissues in the oral cavity, affecting the oral ecological balance and the development of oral diseases, such as caries, apical periodontitis, and periodontitis. Currently, antibiotics are the primary agents against infectious diseases, however, the emergence of drug resistance and the disruption of oral microecology have challenged their applications. The discovery of new antibiotic-independent agents is a promising strategy against biofilm-induced infections. Natural products from traditional medicine have shown potential antibiofilm activities in the oral cavity with high safety, cost-effectiveness, and minimal adverse drug reactions. Aiming to highlight the importance and functions of natural products from traditional medicine against oral biofilms, here we summarized and discussed the antibiofilm effects of natural products targeting at different stages of the biofilm formation process, including adhesion, proliferation, maturation, and dispersion, and their effects on multi-species biofilms. The perspective of antibiofilm agents for oral infectious diseases to restore the balance of oral microecology is also discussed.